Recycling of waste gypsum in preparation of magnesium oxychloride cement (MOC). (1st September 2021) - Gu, Kang; Chen, Bing; Bi, Wanli; Guan, Yan
Abstract: Phosphogypsum (PG) and flue gas desulfurization gypsum (FGDG) are industrial by-products with an annual production of about 30 million tons in China. They are usually treated as solid waste instead of being recycled efficiently. In this study, MgO powder was replaced with waste gypsum by weight of 10%–30% to prepare magnesium oxychloride cement (MOC). The effect of PG and FGDG on the workability and mechanical performance of MOC was evaluated with final setting time, flowability, compressive strength, water resistance, water absorption and volume stability. The hydration mechanism influenced by PG and FGDG was analyzed using X-ray diffraction method and scanning electron microscope. Results showed that PG and FGDG replacement increased the flowability and retarded the setting of the paste, but decreased the compressive strength. PG incorporation effectively improved the water resistance of MOC. The main hydration product in gypsum-free MOC was 5 Mg(OH)2 ·MgCl2 ·8H2 O (phase 5). The addition of PG and FGDG induced the formation of 3 Mg(OH)2 ·MgCl2 ·8H2 O (phase 3). Microstructure observations confirmed that phosphate impurities in untreated PG promoted the nucleation of phase 5 and phase 3 and improved their water stability. The untreated PG showed a better compatibility in MOC system than FGDG. This study could contribute to using waste gypsum to produce a green cementitious material with good performance, thus helping improve the waste resource recycling and achieve the goal of environmental protection. Graphical abstract: Image 1 Highlights: Phosphogypsum (PG) and flue gas desulfurization gypsum (FGDG) are recycled to prepare magnesium oxychloride cement (MOC). The effects of PG and FGDG on the workability and mechanical properties are studied. The hydration mechanism and microstructure of MOC with PG and FGDG are investigated. The improvement of untreated PG on the water resistance of MOC is confirmed.